AB0022 Influence of HLA- DRB1 & DQB1 Alleles on Susceptibility, Clinical Manifestations and Autoantibody Repertoire of Systemic Lupus Erythematosus In South Indian Tamils. (9th June 2015) - Mehra, S.; Mariaselvam, C.M.; Fortier, C.; Krishnamoorthy, R.; Tamouza, R.; Negi, V.S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disorder with a strong genetic background. SLE is characterized by autoantibody production, immune complex deposition and multi-organ damage. The first described genetic link to SLE was the major histocompatibility complex (MHC) on chromosome 6, which codes for HLA. Objectives: The purpose of the present study was to investigate the association of DRB1/DQB1 alleles with disease suseptibility, clinical manifestations and autoantibody profile in South Indian Tamil patients. Methods: A total of 203 SLE patients attending the Clinical Immunology outpatient clinic at JIPMER and 233 healthy ethnicity-matched controls were recruited for the study. Low resolution HLA typing was performed using polymerase chain reaction-sequence specific primer method. Autoantibodies for Extractable nuclear antigens were measured by Immunoblot (Euroimmun, Germany). The allele frequencies between distinct clinical phenotypes and autoantibody subsets were analysed using Chi square test. Pc (Bonferroni) <0.05 were considered statistically significant. Results: We observed that the HLA-DRB1*03 (P=0.01, OR=1.99, Pc=NS), DRB1*15 (P=0.03, OR=1.42, Pc=NS) and DQB1*02 (P=0.04, OR=1.51, Pc=NS) alleles were more frequent among SLE patients than in controls but failed to remain significant after Bonferroni correction similar to HLA-DR*08 (P=0.03, OR=0.39, Pc=NS) which was in the opposite trend. In subgroup analysis of various clinical phenotype variables, association between leucopenia and HLA-DQB1*06 (P=0.01, Pc=0.05, OR=1.75, 95% CI=1.08-2.78) was noted. Influence of HLA on autoantibody subsets revealed that DRB1*15 (Pc=0.03, OR=2.18, 95% CI=1.29-3.6) and DQB1*06 (Pc=0.02, OR=1.89, 95% CI=1.19-3.0) were associated with positivity to RibP and dsDNA respectively. Similarly HLA-DQB1*05 (Pc=0.05, OR=0.55, 95% CI=0.34-0.89 & Pc=0.03, OR=0.52, 95% CI=0.32-0.85) was negatively associated with nucleosome and dsDNA respectively. Our findings on South Indian Tamils are in concordance with the studies on other populations. Conclusions: Our data suggest that HLA-DQB1*06 may serve as a genetic marker for leucopenia in SLE. In addition HLA-DRB1*15 & DQB1*06 may be associated with autoantibodies RibP and dsDNA while DQB1*05 may be protective against Nucleosome and dsDNA. These responses may be attributable to the differences either in antigenic epitopes or amino acid variations in peptide-binding groove or both. References: Al-Motwee S, Jawdat D, Jehani GS, Anazi H, Shubaili A, Sutton P, Uyar AF, Hajeer AH. Association of HLA-DRB1*15 and HLADQB1*06 with SLE in Saudis. Ann Saudi Med. 2013 May-Jun;33(3):229-34. Castaño-Rodríguez N1, Diaz-Gallo LM, Pineda-Tamayo R, Rojas-Villarraga A, Anaya JM. Meta-analysis of HLA-DRB1 and HLA- DQB1 polymorphisms in Latin American patients with systemiclupus erythematosus. Autoimmun Rev. 2008 Feb;7(4):322-30. Disclosure of Interest: None declared